Three-dimensional semiquantitative evaluation of reactive emphysema in magnesium implant models. - Hayashi, Yoshinori; Odagiri, Kazuki; Ishii, Yuji; Yamamoto, Keiichi; Takahashi, Tsuyoshi; Yamashita, Kotaro; Saito, Takuro; Tanaka, Koji; Yamamoto, Kazuyoshi; Makino, Tomoki; Kurokawa, Yukinori; Eguchi, Hidetoshi; et al. (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: Magnesium alloys have great potentials as bioabsorbable implants, whereas the difficulty in evaluating hydrogen gas produced in the degradation process has hindered their research and development. In this study, we investigated the possibility of industrial microfocus X-ray computed tomography (micro-CT) for the precise evaluation of subcutaneous emphysematous changes in a rabbit implantation model. Methods: Magnesium plates with/without porous venting were implanted under skin defects on the backs of rabbits. The graft sites were examined by industrial micro-CT after sacrificing. The captured images were reconstructed three-dimensionally for volumetric analyses. The tissues of the graft site were also examined in the traditional histological investigation. Results: We were able to image and numerate the shape and volume of subcutaneous emphysema using industrial micro-CT. The volume of emphysema was suppressed by pores punched in samples, and this trend increased as the number of pores increased. In the traditional histological examination, inflammatory changes were observed, but the emphysema could not be measured quantitatively. Conclusions: Industrial micro-CT imaging makes it possible to visualize and evaluate magnesium-induced subcutaneous emphysema in animal experiment. This cross-border technology has the potential to be widely applied to other life science fields.